The year in tech 2025 - Condon, Shannon; Menasche, Steven (Ascent Audio, 2024)
Generative AI, biometrics, spatial computing, electric vehicles-new technologies like these are reshaping organizations at the hybrid office, on factory floors, and in the C-suite. What should you and your company be doing now to take advantage of the new opportunities these technologies are creating-and avoid falling victim to disruption? The Year in Tech 2025: The Insights You Need from Harvard Business Review will help you understand what the latest and most important tech innovations mean for your organization and how you can use them to compete and win in today's turbulent business environment.
Online resource; title from title details screen (O'Reilly, viewed October 29, 2024)
Keywords: Business -- Technological innovations; Affaires; Innovations; Audiobooks; Livres audio